2012
DOI: 10.5301/ejo.5000146
|View full text |Cite
|
Sign up to set email alerts
|

Visual function and quality of life in pseudophakic patients before and after capsulotomy

Abstract: Measuring of the outcomes of capsulotomy by clinical indicators alone may underestimate the overall benefits of treatment. Visual acuity in conjunction with visual function and health-related quality of life questionnaires will likely prove to be better indicators of the need for and outcome of capsulotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Although vision can readily be improved with neodymium:Yttrium‐Aluminum‐Garnet (Nd:YAG) laser discission of the opacified posterior capsule, PCO does have an impact on the patients’ quality of life during a period of time (de Juan‐Marcos et al. ; Yotsukura et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Although vision can readily be improved with neodymium:Yttrium‐Aluminum‐Garnet (Nd:YAG) laser discission of the opacified posterior capsule, PCO does have an impact on the patients’ quality of life during a period of time (de Juan‐Marcos et al. ; Yotsukura et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…To complement objective VA information, it is now accepted that the evaluation of the impact of a disease on quality of life using a patient-reported outcome is important for medical interventions, therapeutic decisions, or outcomes research. De Juan-Marcos et al found that the VF-14 scores of patients correlate more strongly with their satisfaction with vision than VA, and VF-14 is more sensitive to functional disability caused by PCO and to capsulotomy improvements, however, improvement in VA is slightly correlated with gains in quality of life [5]. In our current study, regardless of baseline vision, the correspondence between OSI and VF-14 score is very high, while in patients with better baseline vision, the correlation between CDVA and VF-14 is poor.…”
Section: Discussionmentioning
confidence: 99%
“…If the item was not applicable or the subject was unable to complete due to other non-visual factors, the item was deleted and not used for scoring. The higher the score, the lighter the visual impairment [5].…”
Section: Study Design and Analysesmentioning
confidence: 99%
“…40,86,90,91,94,[101][102][103][104][105][106] The included studies were diverse in terms of their aims, comparisons made, study designs, patient characteristics and locations. The full data extraction forms for all included studies are provided (see Appendix 9).…”
Section: Systematic Review Of Health-related Quality-of-life Studiesmentioning
confidence: 99%
“…55 Other measures, such as contrast sensitivity and stereopsis, may be more important than visual acuity for functional tasks, especially in elderly people, 40,106 although they may be less straightforward to assess than visual acuity and may therefore require additional resources if routine tests are to be implemented in clinical practice. The RCTs suggested that stereopsis was more sensitive than visual acuity for indicating changes in vision following second-eye cataract surgery, although they did not indicate any major changes in contrast sensitivity.…”
Section: Other Relevant Factorsmentioning
confidence: 99%